Cover Feature: Aminotriazole Mn(I) Complexes as Effective Catalysts for Transfer Hydrogenation of Ketones (ChemCatChem 20/2018). Issue 20 (24th October 2018) - Martínez‐Ferraté, Oriol; Werlé, Christophe; Franciò, Giancarlo; Leitner, Walter
Abstract : The Cover Feature shows a Mn (I) complex as excellent catalyst for the transfer hydrogenation of ketones with 2‐propanol as hydrogen source. In their Communication, O. Martínez‐Ferraté et al. demonstrate that manganese complexes of readily accessible bidentate triazole ligands are effective catalysts for transfer hydrogenation of a broad range of substrates using iso‐propanol in presence of various bases including sodium hydroxide. The rapidly expanding structural variety of effective ligand frameworks makes cheap and benign Manganese a very attractive new arrow in the quiver of organometallic chemists. More information can be found in the Communication by O. Martínez‐Ferraté et al. onpage 4514 in Issue 20, 2018 (DOI:10.1002/cctc.201800953 ).